FEATURES OF TRADITIONAL MUSICAL CULTURE IN CHINA - Ван, Лівень (SWorldJournal, 2024)
The article examines the peculiarities of traditional musical culture in China and the specifics of the processes associated with its integration into world culture and the adoption of the achievements of European civilisation. The purpose of the article